ECONOMIC IMPACT OF CLIMATE CHANGE ON SMALLHOLDER AGRICULTURE IN COASTAL KENYA: A RICARDIAN APPROACH - Ndunda, Ezekiel (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
ABSTRACT The effect of climate change on agriculture in Kenya is increasingly gaining attention among researchers and policy makers. However, there is scant econometric literature that looks into the relationship between agricultural productivity and climate change in the country. This study evaluates the effect of climate change on both livestock and crop production in the coastal region of Kenya. The specific objectives of this study are: to assess the impact of climate change on crop farming income, to evaluate the impact of climate change on livestock farming income and, to estimate the impact of climate change on combined income from both crop and livestock production. A Ricardian model was used in this study to estimate how mixed agriculture has been affected by the change in climate across the coastal region of Kenya. Results from the study show that climate change significantly (p<0.05) affects net revenues from crops, livestock and a combination of both livestock and crops. The other socioeconomic variable that were found to also significantly (p<0.05) affect net revenue from crops, livestock and a combination of crops and livestock.